Multi-Scale Analysis of Geotechnical and Physicochemical Changes in Loess Caused by Nano-SiO2 Pile Migration - Kong, Ran; Gao, Lei; Zhao, Wenqing; Zhao, Bo (Frontiers in Earth Science, 2021)
Understanding property changes in soil improvement using a new technique is critical for enhancing engineering activity. However, little is known about nano-SiO2 pile-induced changes in soil properties due to its excellent properties as an alternative new additive material. This study aims to examine the changes in properties of loess stabilized with nano-SiO2 pile after curing for 28 days. Using samples taken from four desired radii (i.e., 5, 10 15, and 20 cm), we tested their mineralogical, structural, physicochemical, and index properties and analyzed the relationship of these properties to strengthen the link between microscopic characteristics and macroscopic behaviors. We then discussed the mechanism of the changes in the treated loess properties. The test results show that nano-SiO2 pile induced a physical structure modification in the treated loess and, consequently, an isotropic process with coarser particles due to crystallinity. This resulted in a solidification process in loess with nano-SiO2 pile, causing a decrease in water content and void ratio as well as an increase in natural density, thereby improving its mechanical strength. Meanwhile, the SSA and CEC of treated loess were smaller than those of original loess, and there were slight changes in chemical properties. The interactional relationship of the microscopic and macroscopic observation was facilitated to better understand the mechanism of changes in nano-SiO2 pile-treated loess properties. This finding reveals that nano-SiO2 pile has the potential as an alternative stabilized technique in loess improvement due to its obvious performance improvement and slight chemical changes.